The Effect of Natural Weathering on Mechanical Properties of Silane Treated Bamboo Fibre Reinforced PLA/HDPE Composites for Electrical Insulation Application - Muhammad Izzat Farhan Izham; Ahmad, Mazatusziha (Progress in Engineering Application and Technology, 2024)
Combination of bioplastics with petroleum based plastics are widely used in various type of application due to the increased demand of sustainable products. Thus, this study investigated on the mechanical properties of bamboo fibre reinforced biodegradable PLA/HDPE with a specific focus on the potential as electrical insulation materials. The bamboo fibre was chemically treated with alkali and silane coupling agent for surface modification prior to produce composites via injection moulding at the bamboo fibre composition range from 3% to 7%. The untreated and silane treated bamboo fibre was characterized via Particle Size Analyzer (PSA) and Fourier Transform Infrared Spectrometry (FTIR). Further, the effect of natural weathering on tensile properties of bamboo fibre reinforced PLA/HDPE composites were assessed via Universal Tensile Machine (UTM), in terms of tensile strength, Young’s Modulus and elongation at break. The results showed that 90% (D90) of the product was below than 65.8μm. The presence of C-O, CC-H, Si-O, Si-O-C, and Si-C bonding were successfully discovered from silane treated bamboo fibre using FTIR indicating improvement on hydrophobicity of the bamboo fibre. The optimum results of tensile properties for unweathered composites were untreated 3% of bamboo fibre (P/H/3%) with 2.45MPa, 1365.88MPa and 0.82% for tensile strength, Young’s Modulus and of elongation at break, respectively. The tensile properties increased with increasing bamboo fibre content. A similar trend was observed for the composites which exposed to the natural weathering. Composites at P/H/3% showed the optimum results with 2.05MPa of tensile strength, 1366.20MPa Young’s Modulus and 0.32% of elongation at break. Natural weathering exposure lowers the tensile properties for both untreated and silane treated composites due to occurrence of photo-degradation of the composites. In conclusion, silane treatment and natural weathering greatly affects the tensile properties of bamboo fibre reinforced PLA/HDPE composites.